ANIMASI 3D PERGERAKAN PESAWAT PADA APRON DAN RUNWAY - Retnowati, Nurcahyani Dewi; Kusumaningrum, Anggraini; Kariada, I Made (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2016)
Currently technology development is very fast therefore for getting information quickly and easily is very basic and urgently needed. Learning application that created presents an interactive material with video animated text and sound. This application is made for making easier to understand the management of airports and aircraft movements on the runway by using software 3Ds Max 2010 and Adobe Flash CS3 so that the learning process becomes active, innovative, creative, effective and fun. Application 3D Animation of airplane movement on Apron and Runway have been already running well and got the interpretation criteria of 75,6%, this is evidenced from the results of the test by using questionnaires of 30 respondents stated that the application is running properly.